2014
DOI: 10.1038/ng.3165
|View full text |Cite
|
Sign up to set email alerts
|

BAZ2A (TIP5) is involved in epigenetic alterations in prostate cancer and its overexpression predicts disease recurrence

Abstract: Prostate cancer is driven by a combination of genetic and/or epigenetic alterations. Epigenetic alterations are frequently observed in all human cancers, yet how aberrant epigenetic signatures are established is poorly understood. Here we show that the gene encoding BAZ2A (TIP5), a factor previously implicated in epigenetic rRNA gene silencing, is overexpressed in prostate cancer and is paradoxically involved in maintaining prostate cancer cell growth, a feature specific to cancer cells. BAZ2A regulates numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
141
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 67 publications
11
141
1
1
Order By: Relevance
“…Being a key member of the Drosophila Polycomb group (PcG), EZH2 plays a crucial role in gene expression regulation, maintenance of cell identity, stem cell renewal and oncogenesis. Recent studies have shown that EZH2 overexpression predicts poor patient prognosis and is a frequent event in various cancers, such as breast cancer [1], malignant prostate cancer [2], and hepatocellular carcinoma [3]. There are reports depicting the expression and oncogenic role of EZH2 in lung tumorigenesis [4,5] and EZH2 has been suggested to modulate several pathophysiological processes by promoting cell proliferation and cell cycle progression [6], accelerating cell infiltration and metastasis [7], and inhibiting apoptosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Being a key member of the Drosophila Polycomb group (PcG), EZH2 plays a crucial role in gene expression regulation, maintenance of cell identity, stem cell renewal and oncogenesis. Recent studies have shown that EZH2 overexpression predicts poor patient prognosis and is a frequent event in various cancers, such as breast cancer [1], malignant prostate cancer [2], and hepatocellular carcinoma [3]. There are reports depicting the expression and oncogenic role of EZH2 in lung tumorigenesis [4,5] and EZH2 has been suggested to modulate several pathophysiological processes by promoting cell proliferation and cell cycle progression [6], accelerating cell infiltration and metastasis [7], and inhibiting apoptosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…After tumor cells escape the primary site, the epigenome is subjected to microenvironmental signal modulation, conferring cellular plasticity and adaptability to new and inhospitable conditions (Seftor et al 2006;Hendrix et al 2007;Tam and Weinberg 2013). Indeed, multiple studies have unveiled evidence of specific epigenetic pathways involved in the metastatic progression of different cancer types (Cunha et al 2014;Gu et al 2015;Okada et al 2015;Tang et al 2015). Therefore, the combination of genetic and epigenetic events during the course of metastasis likely determines the acquisition of MIC traits.…”
Section: G464vmentioning
confidence: 99%
“…(for review, see McStay and Grummt 2008). Interestingly, TIP5 (also known as BAZ2A) is overexpressed in prostate cancer and is involved in maintaining prostate cancer cell growth by directly interacting with EZH2 to maintain epigenetic silencing at Pol II transcribed genes repressed in metastasis (Gu et al 2015). This is a somewhat paradoxical result, since up-regulation of ribosome biogenesis is a feature of most cancers.…”
Section: The Pol I Transcription Machinerymentioning
confidence: 99%